STATE AND DEVELOPMENT PROSPECTS OF GERMANY CONSULTING MARKET IN THE CONTEXT OF EUROPE-WIDE TRENDS - K. Kovalska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper deals with the actual state of consulting market in Germany. The structural configuration of the Germany consulting market on functional grounds, with the customer's branch, as well as geographically were analyzed. The main prospects of German consulting market development in the context of Europe-wide trends have been defined.